Dietary Patterns in Alzheimer’s Disease. Preventive Role of L-carnitine and Supplementation with L-Carnitine and Its Derivatives - Alina Kepka; Agnieszka Ochocinska; Malgorzata Borzym-Kluczyk; Ewa Skorupa; Beata Stasiewicz-Jarocka; Sylwia Chojnowska; Napoleon Waszkiewicz (Challenges in Disease and Health Research Vol. 9, 2021)
The prevention or treatment of neurodegenerative disorders, such as Alzheimer’s disease (AD), is a difficult task for modern health care. The purpose of this chapter was to review the literature on the prevention or alleviation of AD by introducing an appropriate carnitine-rich diet, dietary carnitine supplements and the MIND (Mediterranean-DASH Intervention for Neurodegenerative Delay) diet, which contains elements of the Mediterranean diet and the Dietary Approaches to Stop Hypertension (DASH) diet. L-carnitine (LC) plays a crucial role in the energetic metabolism of the cell. A properly balanced diet contains a substantial amount of LC as well as essential amino acids and microelements taking part in endogenous carnitine synthesis. In healthy people, carnitine biosynthesis is sufficient to prevent the symptoms of carnitine deficiency. In persons with dysfunction of mitochondria, e.g., with AD connected with extensive degeneration of the brain structures, there are often serious disturbances in the functioning of the whole organism. The Mediterranean diet is characterized by a high consumption of fruits and vegetables, cereals, nuts, olive oil, and seeds as the major source of fats, moderate consumption of fish and poultry, low to moderate consumption of dairy products and alcohol, and low intake of red and processed meat. The introduction of food stuffs rich in carnitine and the MIND diet or carnitine supplementation of the AD patients may improve their functioning in everyday life. It should be stressed that correct nutrition is an important element of lifestyle that may be an important factor for healthy, slow, favorable aging and delaying the development of neurodegenerative diseases including dementia and AD.